Peningkatan Kompetensi Bidang Karya Tulis Ilmiah Bagi Guru SMK - Chairani, Rifda (Penerbit Goodwood, 2025)
Purpose:This community service program aims to improve the competence of vocational high school (SMK) teachers in writing scientific papers. The initiative responds to the increasing demand for teachers to produce academic works, both as part of their professional development and as a requirement for career advancement, in line with government regulations on teacher functional positions and credit points. Method:The program was conducted through a workshop model combining theoretical sessions, practical writing exercises, and mentoring. Participants were guided step-by-step in developing scientific papers, from topic selection, literature review, and methodology design to data analysis and manuscript preparation. Mentoring was provided intensively to ensure each participant could produce a draft ready for submission to scientific journals. Results: The workshop significantly enhanced teachers’ understanding of scientific writing principles, improved their ability to structure and present ideas systematically, and increased their confidence in publishing academic work. Several participants successfully completed manuscripts that met the standards of accredited journals. Conclusion:Capacity-building programs in scientific writing effectively strengthen teacher professionalism and support their career advancement. Continuous training and mentoring are crucial to sustaining these improvements. Limitation:The program’s impact was limited to a specific group of SMK teachers in Cibinong, making generalization to other regions less certain. Follow-up studies are needed to measure the long-term sustainability of skills gained. Contribution:This program provides a practical model for teacher professional development through targeted scientific writing training, integrating theory, practice, and mentorship to produce measurable outputs in academic publication readiness.